BIO-EFFICACY OF NEWER FUNGICIDE TRIFLOXYSTROBIN 25% PLUS TEBUCONAZOLE 50% WG (NATIVO 75 WG) AGAINST ANTHRACNOSE LEAF SPOT AND POD BLIGHT OF SOYBEAN - BIJENDER KUMAR, (The Bioscan, 2019)
Evaluation of the efficacy of trifloxystrobin 25% + tebuconazole 50% (Nativo 75 WG) against Colletotrchum truncatum causing anthracnose leaf spot and pod blight disease and investigation on phytotoxicity of the fungicide on soybean were carried out during experimentation. Summarisation of results indicated that two foliar sprays of trifloxistrobin 25% + tebuconazole 50% @ 350g/ha, first at the time of appearance of the disease and second its 14 days later was found to be the best provided 78.06% disease control and recorded highest grain yield (1059.26kg/ha) and increase in grain yield (62.87%). However, it was found to be significantly at with the same fungicide applied @ 300g/ha, provided 74.86% control of the disease and recorded 60.31% increase in grain yield over control. Moreover, the chemical was found to be safe as no phytotoxic effect of test fungicide was noticed on soybean even at the highest dose (1400g/ha) tested.